Menstrual Exclusions in Nepal: Some Evidence of Transition - Subedi, Madhusudan; Parker, Sara (Dhaulagiri Journal of Sociology and Anthropology, 2021)
There is a long history of menstrual restrictions, stigmas and taboos across nearly all religions, regions and cultures. The origins of myths and misconceptions have often been linked to various religious texts and women were prohibited from participating in normal life while menstruating. Culturally, in many parts of the world, menstruation is still considered ‘dirty’ and ‘impure’, although this is not true. Menstruation is often associated with feelings of shame, horror, danger, disgust, and sin. There have been initiatives to change the perception that menstruating women are not polluted, thus bringing an end to traditional customs such as not being allowed to sleep in their own home or touch male relatives to more extreme forms of isolation such as being confined to the ‘cow shed’. This paper draws on research conducted between 2019 and 2021 under a British Academy-funded Global Challenge Research Fund project entitled ‘Dignity Without Danger’. The study employed qualitative methods, covering 160 qualitative interviews and 16 focus group discussions among different caste and ethnic groups in three different ecological areas (mountain, hill, and tarai) in seven provinces in Nepal. Today, menstruating women have relatively more freedom to discuss this topic due to increased awareness that menstruation is a natural process. However, our study shows there are still differences between cultures, religions, castes and ethnic groups, and regions, and a single narrative does not represent the issues related to menstrual exclusion in Nepal. The study shows that many menstruating girls and women are still restricted in a number of diverse ways, from not offering prayers, entering or worshiping in temples, touching holy books, and participating in religious rituals. In some areas, more extreme practices persist which discriminate against women when menstruating. Our research highlights that education and an interdisciplinary, multisector approach are required if menstrual discrimination is to be addressed. Finally, this paper emphasizes the necessity for providing correct knowledge about menstruation to the entire community including elders, males and religious leaders as well as adolescents and young girls. Such knowledge will help them practice safe and hygienic menstrual practices, challenge and reduce their traditional beliefs, misconceptions and restrictions regarding menstruation that are essential to achieving menstrual dignity.